Association of the Yips and Musculoskeletal Problems in Highly Skilled Golfers: A Large Scale Epidemiological Study in Japan - Yasufumi Gon; Daijiro Kabata; Sadahito Kawamura; Masahito Mihara; Ayumi Shintani; Ken Nakata; Hideki Mochizuki (Sports, 2021)
The yips are a set of conditions associated with intermittent motor disturbances that affect precision movement, especially in sports. Specifically, skilled golfers suffer from the yips, although its clinical characteristics and pathophysiology have not been well-studied. We surveyed skilled golfers to characterize their yips-related symptoms, to explore potential confounding factors associated with the yips. Golfers’ demographic information, golfing-career-related history, musculoskeletal status and manifestations of the yips are surveyed. Among the 1576 questionnaires distributed, 1457 (92%) responses were received, of which 39% of golfers had experienced the yips. The median age and golfing careers were 48 and 28 years, respectively. Golfers who had experienced the yips were older and had longer golfing careers and more frequent musculoskeletal problems than those without experience of the yips. The multivariate logistic regression analysis revealed that a longer golfing career and musculoskeletal problems were independent factors associated with yips experience. More severe musculoskeletal problems were associated with higher odds of experiencing the yips. A positive association between the yips and musculoskeletal problems was also observed. The yips have similar characteristics to task-specific movement disorders, with a detrimental effect caused by excessive repetition of a routine task. These findings support the notion that the yips are a type of task-specific dystonia.